2021
DOI: 10.21037/atm-21-4080
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV protects cardiomyocytes against hypoxia injury via HIF-1α and the JAK2/STAT3 pathway

Abstract: Background: Hypoxia is an important cause of myocardial injury due to the heart's high susceptibility to hypoxia. Astragaloside IV (AS-IV) is the main component of Astragalus membranaceus and could exert cardiac protective role. Here, the effect of AS-IV on hypoxia-injured H9c2 cardiomyocytes was elucidated. Methods: First, H9c2 cells were exposed to hypoxia and/or AS-IV treatment. Cell apoptosis, death, and viability as well as hypoxia-inducible factor 1α (HIF-1α) expression and apoptotic proteins were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Under hypoxia, HIF‐1α is stabilized and translocated to the nucleus, where it forms a complex with HIF‐1β and thus initiates the transcription of target genes. [ 15,16 ] The expression level of HIF‐1α in human aortic dissection tissues is prominently elevated. [ 17 ] Therefore, it is necessary to clarify the impact of HIF‐1α on AD development.…”
Section: Introductionmentioning
confidence: 99%
“…Under hypoxia, HIF‐1α is stabilized and translocated to the nucleus, where it forms a complex with HIF‐1β and thus initiates the transcription of target genes. [ 15,16 ] The expression level of HIF‐1α in human aortic dissection tissues is prominently elevated. [ 17 ] Therefore, it is necessary to clarify the impact of HIF‐1α on AD development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some researchers have pointed out that JAK/STAT3-regulated fatty acid β-oxidation is also crucial for BCSC self-renewal and chemotherapy resistance ( 57 ). A study on the mechanism of ASIV have shown that ASIV may relieve myocardial cell damage after hypoxia by activating JAK2/STAT3-mediated HIF-1α signaling ( 58 ). In addition, ASIV can inhibit the Notch signaling pathway and PI3K/Akt/mTOR signaling pathway ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this signaling pathway may accomplish signal transduction from extracellular factors to the nucleus ( 27 , 28 ). It has been demonstrated that JAK/STAT signaling pathway is involved in many important physiological activities, such as cell proliferation, differentiation, immune regulation, and apoptosis ( 29 31 ).…”
Section: Jak/stat Signaling Pathwaymentioning
confidence: 99%